Risk factors associated with stress, anxiety, and depression among university undergraduate students - Mohammad Mofatteh (AIMS Press, 2021)
It is well-known that prevalence of stress, anxiety, and depression is high among university undergraduate students in developed and developing countries. Students entering university are from different socioeconomic background, which can bring a variety of mental health risk factors. The aim of this review was to investigate present literatures to identify risk factors associated with stress, anxiety, and depression among university undergraduate students in developed and developing countries. I identified and critically evaluated forty-one articles about risk factors associated with mental health of undergraduate university students in developed and developing countries from 2000 to 2020 according to the inclusion criteria. Selected papers were analyzed for risk factor themes. Six different themes of risk factors were identified: psychological, academic, biological, lifestyle, social and financial. Different risk factor groups can have different degree of impact on students' stress, anxiety, and depression. Each theme of risk factor was further divided into multiple subthemes. Risk factors associated with stress, depression and anxiety among university students should be identified early in university to provide them with additional mental health support and prevent exacerbation of risk factors.